1994
DOI: 10.1007/bf02390684
|View full text |Cite
|
Sign up to set email alerts
|

Differential antibiotic-induced release of endotoxin from gram-negative bacteria

Abstract: Treatment of log phase cultures of Escherichia coli with cell wall active antibiotics results in increased exposure of immunologically reactive lipid A epitopes of lipopolysaccharide (LPS) and release of soluble LPS into culture supernatants. Comparison of the efficacy of two cell wall active antibiotics, ceftazidime, a penicillin-binding protein 3 selective antibiotic, and imipenem, a penicillin-binding protein 2 selective antibiotic, for their relative efficacy in mediating LPS release indicated quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…Such enlargements were not seen in ofloxacin-or trimethoprim-induced filaments or untreated bacteria. Because increased levels of endotoxin production have been observed to be induced by both B. pseudomallei (31) and many other filamentous gram-negative bacteria (5,6,11,17) during antibiotic treatment for sepsis caused by gramnegative bacteria and because most of these antibiotics affect the bacterial cell wall through PBP 3, we think that the enlargement of the periplasmic space observed in ceftazidimeinduced filaments could be structural features resulting from increased levels of endotoxin production.…”
Section: Discussionmentioning
confidence: 94%
“…Such enlargements were not seen in ofloxacin-or trimethoprim-induced filaments or untreated bacteria. Because increased levels of endotoxin production have been observed to be induced by both B. pseudomallei (31) and many other filamentous gram-negative bacteria (5,6,11,17) during antibiotic treatment for sepsis caused by gramnegative bacteria and because most of these antibiotics affect the bacterial cell wall through PBP 3, we think that the enlargement of the periplasmic space observed in ceftazidimeinduced filaments could be structural features resulting from increased levels of endotoxin production.…”
Section: Discussionmentioning
confidence: 94%
“…A direct link between endotoxin release and TNFα-liberation from monocytes has also recently been demonstrated in different in vitro systems [61,25] Differences in the endotoxin-liberating potential of antibiotics An important step in understanding treatment-related endotoxin release was the finding that different classes of antimicrobial substances led to different levels of circulating endotoxin. Since then, many investigators have demonstrated both in vitro and in vivo that the use of certain antibiotics leads to significantly increased levels of free endotoxins while others produce relatively low amounts [16,62,63,64,65,66,67,68]. The amount of LPS, LOS, LTA or sPG is obviously dependent on the type and number of invading bacteria.…”
Section: Antibiotic-induced Release Of Bacterial Cell Wall Componentsmentioning
confidence: 99%
“…For example, EDTA, tris-buffer, or saline promote OM release [7,25,22]. The presence of antibiotics [26], phage infection [6,27], increased temperature [28], and amino acid depletion [20] also enhance the release. However, LPS synthesis was shown to be regulated by the stringent control mechanism, and amino acid deprivation stimulated the rate of LPS release in relA mutants but not in relA + strains [21].…”
Section: Release Of Om Componentsmentioning
confidence: 99%